2010
DOI: 10.1111/j.1365-313x.2010.04416.x
|View full text |Cite
|
Sign up to set email alerts
|

OsPUB15, an E3 ubiquitin ligase, functions to reduce cellular oxidative stress during seedling establishment

Abstract: SUMMARYThe plant U-box (PUB) protein functions as an E3 ligase to poly-ubiquitinate a target protein for its degradation or post-translational modification. Here, we report functional roles for OsPUB15, which encodes a cytosolic U-box protein in the class-II PUB family. Self-ubiquitination assays showed that bacterially expressed MBPOsPUB15 protein has E3 ubiquitin ligase activity. A T-DNA insertional mutation in OsPUB15 caused severe growth retardation and a seedling-lethal phenotype. Mutant seeds did not pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
82
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 117 publications
(91 citation statements)
references
References 72 publications
(70 reference statements)
5
82
0
Order By: Relevance
“…They have various functions related to biotic and abiotic stress responses (Yang et al, 2006;Cho et al, 2008;Trujillo et al, 2008;Liu et al, 2011), hormonal responses (Luo et al, 2006;Raab et al, 2009), self-incompatibility (Liu et al, 2007;Samuel et al, 2008Samuel et al, , 2009, and seed germination (Bergler and Hoth, 2011;Salt et al, 2011). U-box E3s also have cellular functions within a diverse group of monocot and dicot model crops, such as Brassica spp., Medicago spp., rice (Oryza sativa), tobacco (Nicotiana tabacum), and tomato (Solanum lycopersicum) plants (Gu et al, 1998;Stone et al, 1999Stone et al, , 2003Zeng et al, 2004Zeng et al, , 2008GonzĂĄlez-Lamothe et al, 2006;Vega-SĂĄnchez et al, 2008;Bos et al, 2010;Mbengue et al, 2010;Park et al, 2011b), suggesting that they are widely conserved in the plant kingdom.…”
mentioning
confidence: 99%
“…They have various functions related to biotic and abiotic stress responses (Yang et al, 2006;Cho et al, 2008;Trujillo et al, 2008;Liu et al, 2011), hormonal responses (Luo et al, 2006;Raab et al, 2009), self-incompatibility (Liu et al, 2007;Samuel et al, 2008Samuel et al, , 2009, and seed germination (Bergler and Hoth, 2011;Salt et al, 2011). U-box E3s also have cellular functions within a diverse group of monocot and dicot model crops, such as Brassica spp., Medicago spp., rice (Oryza sativa), tobacco (Nicotiana tabacum), and tomato (Solanum lycopersicum) plants (Gu et al, 1998;Stone et al, 1999Stone et al, , 2003Zeng et al, 2004Zeng et al, , 2008GonzĂĄlez-Lamothe et al, 2006;Vega-SĂĄnchez et al, 2008;Bos et al, 2010;Mbengue et al, 2010;Park et al, 2011b), suggesting that they are widely conserved in the plant kingdom.…”
mentioning
confidence: 99%
“…37 Another study verified that OsPUB15 (Plant U-box 15) overexpression, which encodes a cytosolic protein from class II PUB family that contains a U-box domain, is regulated by environmental stresses. 40 Plant proteins that contain a U-box domain belong to the E3 ligase family that assists the poly-ubiquitination of target proteins in degradation or mono-ubiquitination and subsequent modification of the target proteins localization or activity. 41 It was found that OsPUB15 is induced by several stresses and avoid tissue damages.…”
Section: Genes Involved In Multiple Abiotic Stressesmentioning
confidence: 99%
“…41 It was found that OsPUB15 is induced by several stresses and avoid tissue damages. 40 OsPUB15 maintains the viability of meristematic cells, protecting them from osmotic stress during germination and growth of rice plants, as well as reducing the levels of ROS produced in the presence of abiotic stresses. 40,42 OsPUB15 expression levels increased in the presence of hydrogen peroxide (H 2 O 2 ), high salinity and drought, indicating that PUB15 is an important regulator of ROS levels and stress responses.…”
Section: Genes Involved In Multiple Abiotic Stressesmentioning
confidence: 99%
“…The relatively large number of plant U-box E3 ligases implies that these enzymes have indispensable roles in diverse cellular responses that are specific to plants. According to recent studies, plant U-box E3 ligases function in responses to abiotic and biotic stress (Cho et al 2008;Bergler and Hoth 2011;Liu et al 2011b;Lu et al 2011;Park et al 2011;Seo et al 2012a), responses to hormones (Raab et al 2009;Seo et al 2012a;Hu et al 2013;Sakamoto et al 2013), growth and development Wang et al 2013), and self-incompatibility (Liu et al 2007;Samuel et al 2008Samuel et al , 2009Zhang et al 2014). Although various roles of different U-box E3s have been studied, functional elucidation related to plant-specific environmental stress response mechanisms of U-box proteins is still insufficient.…”
Section: Introductionmentioning
confidence: 99%